2015
DOI: 10.4238/2015.june.29.7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early postoperative enteral nutrition on clinical outcomes in patients with gastric cancer

Abstract: The impact of early enteral nutrition (EEN) on clinical outcomes of gastric cancer patients was investigated. Three hundred pa-tients undergoing gastric cancer surgery from July 2010 to May 2014 were randomly divided into experimental and control groups (n = 150/group). Experimental group patients received enteral nutrition in water during the early postoperative period. Control group patients received conventional perioperative treatment. Patients' clinical outcomes, post-operative immune function, and nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 9 publications
0
29
0
1
Order By: Relevance
“…Palumbo et al reported that lymphatic metastasis, but not primary tumor growth or angiogenesis, was diminished in fibrinogen-deficient mice, suggesting that Fib was a critical determinant of the metastatic potential by impeding elimination of tumor cell by natural killer cell [ 19 , 20 ]. Thirdly, serum Alb was one of the most widely used markers for reflecting nutritional status and hypoproteinmia was reported as a crucial parameter of malnutrition and directly influenced prognosis of GC; low levels of Alb and pAlb levels have an impact on determinant of immune responses and malnutrition, which could impair immune system defending against GC [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Palumbo et al reported that lymphatic metastasis, but not primary tumor growth or angiogenesis, was diminished in fibrinogen-deficient mice, suggesting that Fib was a critical determinant of the metastatic potential by impeding elimination of tumor cell by natural killer cell [ 19 , 20 ]. Thirdly, serum Alb was one of the most widely used markers for reflecting nutritional status and hypoproteinmia was reported as a crucial parameter of malnutrition and directly influenced prognosis of GC; low levels of Alb and pAlb levels have an impact on determinant of immune responses and malnutrition, which could impair immune system defending against GC [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…From outside Japan, we found one RCT and three retrospective studies concerning early diet after gastrectomy published in or after 2014, and two of them focused on total gastrectomy . All four papers mentioned the feasibility and safety of early oral feeding after gastrectomy.…”
Section: Consensus Guidelines For Enhanced Recovery After Gastrectomymentioning
confidence: 99%
“…Patients with early enternal nutrition (EEN) showed significantly shorter hospital stay (16.2 [± 3.6]/19.7 [± 4.5] days, p < 0.001) and time until flatus (2.2 [± 0.3]/3.7 [± 0.5] days, p < 0.001 [ 22 ]), whereas no significant differences were found between EEN and total parental nutrition (TPN) [ 23 ]. Compared to traditional perioperative treatment (TP) (e.g., nasoenteral feeding tube and postoperative intravenous infusion), hospital stay (7.73 [± 2.13]/9.77 [± 1.76] days, p = 0.002), time until flatus (78.8 [± 9.3]/85.3 [± 8.4] hours, p = 0.011), and duration of fever (80.2 [± 6.0]/88.1 [± 8.1] hours, p = 0.012) were also shorter in patients with EEN [ 24 ].…”
Section: Resultsmentioning
confidence: 99%